2019
DOI: 10.1093/brain/awy330
|View full text |Cite|
|
Sign up to set email alerts
|

Key role of SMN/SYNCRIP and RNA-Motif 7 in spinal muscular atrophy: RNA-Seq and motif analysis of human motor neurons

Abstract: The molecular mechanisms responsible for selective motor neuron loss in SMA remain elusive. Rizzo et al. show that deregulated transcripts in SMA-motor neurons share motif 7, targeted by SYNCRIP, which binds SMN. Impaired SYNCRIP-SMN interaction leads to dysregulation of downstream genes, such as NEUREXIN2, which could represent therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 60 publications
6
32
2
Order By: Relevance
“…We analyzed mRNA expression of four independent D2KO motor neuron cultures, four D10KO (clone G4) motor neuron cultures and eight independent cultures of the parental control motor neurons. Comparison of our parental motor neuron RNA sequencing dataset by principal component analysis (PCA) to available human iPSC-motor neuron datasets (GSE108094 (Rizzo et al, 2019), GSE121069 (Nijssen et al, 2018)) and laser captured post mortem human motor neuron datasets (GSE76220 (Batra et al, 2016), GSE76514 (Nichterwitz et al, 2016), GSE93939 (Allodi et al, 2019)) showed tight clustering of our 8 samples together, supporting consistent, high-quality differentiation conditions of our cultures ( Figure 4A). Interestingly, PCA of all of our samples alone showed that the expression profiles of D2KO and D10KO motor neurons complete overlapped and were separate from parental control motor neurons ( Figure 4B).…”
Section: Chchd10 and Chchd2 Knockout Motor Neurons Have Overlapping Tsupporting
confidence: 70%
See 1 more Smart Citation
“…We analyzed mRNA expression of four independent D2KO motor neuron cultures, four D10KO (clone G4) motor neuron cultures and eight independent cultures of the parental control motor neurons. Comparison of our parental motor neuron RNA sequencing dataset by principal component analysis (PCA) to available human iPSC-motor neuron datasets (GSE108094 (Rizzo et al, 2019), GSE121069 (Nijssen et al, 2018)) and laser captured post mortem human motor neuron datasets (GSE76220 (Batra et al, 2016), GSE76514 (Nichterwitz et al, 2016), GSE93939 (Allodi et al, 2019)) showed tight clustering of our 8 samples together, supporting consistent, high-quality differentiation conditions of our cultures ( Figure 4A). Interestingly, PCA of all of our samples alone showed that the expression profiles of D2KO and D10KO motor neurons complete overlapped and were separate from parental control motor neurons ( Figure 4B).…”
Section: Chchd10 and Chchd2 Knockout Motor Neurons Have Overlapping Tsupporting
confidence: 70%
“…RNA-seq data from the motor neurons in this study were contrasted to publicly available datasets of other human iPSC derived motor neurons; GSE108094 (Rizzo et al, 2019) and GSE121069 (Nijssen et al, 2018) as well as laser captured motor neurons; GSE76220 (Batra et al, 2016), GSE76514 (Nichterwitz et al, 2016) and GSE93939 (Allodi et al, 2019). The same analysis procedures (trimming, mapping and read counting) were applied to the reference samples as for our dataset.…”
Section: Rna Sequencingmentioning
confidence: 99%
“…Among the complex members, HNRNPU was previously identified as one of five top-ranked RNA binding proteins, showing significant alterations in the motor neurons, cerebellum and spinal cords of ALS patients compared to the control, and co-localizes with cytoplasmic TDP-43 aggregates [64,65]. Moreover, we observed in SALS2 motor cortexes vs. control a down-regulation of SYNCRIP, whose overexpression was previously found to ameliorate spinal muscular atrophy pathological phenotypes [66].…”
Section: Crd-mediated Mrna Stability Complexsupporting
confidence: 56%
“…In mammals, different domains mediate the interaction of SYNCRIP with different effectors, which renders SYNCRIP a wide range of functions including circadian regulation [45][46][47], neuronal morphogenesis [48][49][50], and stress response [51]. Misregulation of SYNCRIP has been reported in neurodegenerative diseases [52,53], psychiatric disorders [54,55], and cancer [56,57]. In flies, studies have shown that Syp is required for different developmental phenotypes, such as oogenesis [28], maintaining a normal structure and function of synapses at the neuromuscular junction in larvae [29,30], and determining neuron/glia cell fates [31,32].…”
Section: Discussionmentioning
confidence: 99%